2014
DOI: 10.1002/cctc.201402523
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Palladium Catalysts for the Heck Reaction by Support Functionalization and Solvent Selection

Abstract: Pd nanoparticles were synthesized on nonfunctionalized and functionalized SBA‐15 grafted with thiol or amine groups. The resulting materials were used as catalysts to study the influence of these functional groups for a similar Pd particle size of approximately 2 nm on the Heck reaction that uses iodide substrates. The nonfunctionalized catalysts lost their activity quickly because of Pd leaching and particle growth. However, if a mixed solvent that consisted of toluene and DMF was used and thiol groups were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…One of the most important advances in this eld is developing hybrid systems through functionalization of mesoporous silica materials. [51][52][53][54][55][56] In this context using sulfur, [57][58][59][60][61][62] phosphorous and amine-based functional groups 63,64 has attracted growing attention and resulted in introducing novel hybrid systems [65][66][67][68] with outstanding utilities for catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important advances in this eld is developing hybrid systems through functionalization of mesoporous silica materials. [51][52][53][54][55][56] In this context using sulfur, [57][58][59][60][61][62] phosphorous and amine-based functional groups 63,64 has attracted growing attention and resulted in introducing novel hybrid systems [65][66][67][68] with outstanding utilities for catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd nanoparticles were immobilized on N‐ or S‐ functionalized GO using a modified method described by de Jong et al . By this protocol the solid support is capable of removing Pd species from solution.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors report that functional groups, such as thiol and amine groups, grafted on ordered mesoporous silica and fumed silica are able to reduce Pd leaching in Heck and Suzuki reactions . Shimizu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that during the Suzuki reaction, leached Pd species formed during catalysis are of considerable importance for the conversion of reactants to Catalysis Science & Technology Paper products, thus, the actual catalytic species are in solution. 57,[63][64][65][66][67] However, this is a controversial subject because other authors have reported that C-C coupling reactions take place preferentially on the metal particle surface, thus in a heterogeneous fashion. 56,[68][69][70] We used the PVP test to investigate the leaching process.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%